Solidarność jako wartość w kazaniach księdza Jerzego Popiełuszki w kontekście artykułów z „Trybuny Ludu” - Zalewska, Krystyna (Słowo. Studia językoznawcze, 2010)
In the article I analysed and interpreted the language of political sermons delivered by Jerzy Popiełuszko in the years 1982-1984. He is one of the most recognizable symbols of anticommunist opposition in Poland in the 1980s. His speeches are exceptionally interesting as regards the “language of values”. The present study concerns only one aspect of the issue, i.e. language in which solidarity is expressed. It is necessary to take into consideration ambiguity of this word (solidarity is the name of an attitude as well as the trade union). One should pay attention to the relations between the discussed category and sacredness or suffering. It is also significant that the sermons are marked with emotions. The priest did not keep his audience at a distance. He used many metaphors, comparisons, hyperboles and metonymies to reach the faithful. The solidarity is described by him as the most important value in the 1980s in Poland. The priest emphasized the role of this value in social and political situation of the time. I also discussed the “language of values” in propaganda articles from "Trybuna Ludu”. This comparison let me draw a conclusion that in both cases authors used similar language to express completely different ideas. This article is a part of my M.A. thesis, in which the language of all the categories of values (according to Jadwiga Puzynina) in Popiełuszko sermons and articles from Trybuna Ludu” is discussed.